Estudo experimental do limão Tahiti (Citrus latifólia Tanaka): composição físico-química e de minerais da polpa in natura e do resíduo albedo - Kátia Davi Brito; Josenildo Isidro Santos Filho; Henrique Bruno Lima; Emmanuel Paixao Neto; Flávia Cristina dos Santos Lima (Revista Principia, 2017)
The present work aimed to evaluate the physical-chemical and mineral parameters of the in natura pulp and the albedo residue of the Tahiti lemon. The pulp was extracted on a stainless steel horizontal removing device and refined in a sieve with a mesh size less than 1.0 mm. The albedo residue was separated and manually dried in a kiln with forced air circulation at a temperature of 55 ± 2°C until constant mass. The physico-chemical analyzes for the pulp in natura were: total solids (TS), soluble solids (°Brix), titratable acidity (TA), pH, vitamin C, total and reducing sugars, moisture, ashes and water activity. For the dry albedo, moisture, pH, ashes, water activity, protein, reducing sugars (RS) and pectin were evaluated. The mineral constituents consisted on the evaluation of the centesimal composition of calcium (Ca), potassium (K), phosphorus (P), manganese (Mn), iron (Fe), zinc (Zn) and copper (Cu) for the in natura pulp and dry albedo residue of Tahiti lemon. Regarding the physical-chemical and mineral quality parameters, results were satisfactory. Therefore, the study of Tahiti lemon provided essential information on the availability of nutrients, so as to provide the consumer with new products derived from the Tahiti lemon and also to add economic value to the fruit.